Acceptability and content validity of suicidality screening items: a qualitative study with perinatal women - Dudeney, Elizabeth; Coates, Rose; Ayers, Susan; McCabe, Rose (Frontiers in Psychiatry, 2024)
Background Suicide is a leading cause of death for perinatal women. It is estimated that up to 50% of women with mental health issues during pregnancy and/or after birth are not identified, despite regular contact with healthcare services. Screening items are one way in which perinatal women needing support could be identified. However, research examining the content validity and acceptability of suicide-related screening items with perinatal women is limited. Aims This study sought to: (i) assess the acceptability and content validity of 16 suicide-related items that have been administered and/or validated in perinatal populations; and (ii) explore the potential barriers and facilitators that may affect how women respond to these items when administered during pregnancy and after birth. Methods Twenty-one cognitive and semi-structured interviews were conducted with pregnant and postnatal women in the UK. The sample included women who had experienced self-reported mental health problems and/or suicidality during the perinatal period, and those who had not. Interviews were transcribed verbatim, and a coding framework based on the Theoretical Framework of Acceptability was applied to explore the data using deductive and inductive approaches. Results Findings indicated that the acceptability and content validity of suicide-related items were largely unacceptable to perinatal women in their current form. Women found terms such as ‘better off dead’ or ‘killing myself’ uncomfortable. Most women preferred the phrase ‘ending your life’ as this felt less confronting. Comprehensibility was also problematic. Many women did not interpret ‘harming myself’ to include suicidality, nor did they feel that abstract language such as ‘leave this world’ was direct enough in relation to suicide. Stigma, fear, and shame was central to non-disclosure. Response options and recall periods further affected the content validity of items, which created additional barriers for identifying those needing support. Conclusions Existing suicide-related screening items may not be acceptable to perinatal women. Maternity practitioners and researchers should consider the phrasing, clarity, context, and framing of screening items when discussing suicidality with perinatal women to ensure potential barriers are not being reinforced. The development of specific suicidality screening measures that are acceptable, appropriate, and relevant to perinatal women are warranted.